2009
DOI: 10.1038/ismej.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of iron-reducing microorganisms in anoxic rice paddy soil by 13C-acetate probing

Abstract: In anoxic rice field soil, ferric iron reduction is one of the most important terminal electron accepting processes, yet little is known about the identity of iron-reducing microorganisms. Here, we identified acetate-metabolizing bacteria by RNA-based stable isotope probing in the presence of iron(III) oxides as electron acceptors. After reduction of endogenous iron(III) for 21 days, isotope probing with 13 C-labeled acetate (2 mM) and added ferric iron oxides (ferrihydrite or goethite) was performed in rice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(160 citation statements)
references
References 68 publications
8
151
0
1
Order By: Relevance
“…This was similar to the previous studies that have reported the enrichment of Geobacter species in aquifer sediments by the addition of humics and other extracellular quinones [43]. The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was similar to the previous studies that have reported the enrichment of Geobacter species in aquifer sediments by the addition of humics and other extracellular quinones [43]. The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45].…”
Section: Discussionsupporting
confidence: 88%
“…Geobacter species are the prevalent microbes capable of quinones respiration in anaerobic soils and sediments [10]. Being the predominant acetate-consuming microorganisms in paddy soil [17], Geobacter species are strong competitors for methanogenic substrates. As the important organic TEAs for Geobacter species, the effect of different concentrations of quinones on methanogenesis has been studied in granular sludge [8], but the impact in paddy soil is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…All members of the Desulfuromonadales are able to reduce iron and manganese oxides and are also frequently found in clone libraries of marine sediments (for example, Ravenschlag et al, 1999;Bowman and McCuaig, 2003;Mu mann et al, 2005). Desulfuromonadalesrelated organisms can be easily enriched in sediments or microbial fuel cells by acetate addition (Snoeyenbos-West et al, 2000;Bond et al, 2002; Manganese-reducing bacteria in marine sediments V Vandieken et al Holmes et al, 2002;Holmes et al, 2004;Vandieken et al, 2006a) but have also been identified as ironreducing bacteria by cultivation-independent SIP studies with 13 C-acetate in rice field soil and uranium-contaminated aquifer (Chang et al, 2005;Hori et al, 2010). Our finding of Desulfuromonadales in MPN enrichments coincided with their detection in clone libraries of heavy SIP fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly in SIP incubations with only one dominating electronaccepting process, selective isotopic enrichment of nucleic acids strongly suggests that the microorganisms harboring these heavy nucleic acids are the ones that catalyze this process. With this technique, members of the order Desulfuromonadales were identified to couple dissimilatory iron reduction to the oxidation of 13 C-acetate in a uranium-contaminated aquifer and rice field soil (Chang et al, 2005;Hori et al, 2010). Other bacteria, which became isotopically labeled by metabolizing 13 C-labeled substrates under iron-reducing conditions, belonged to members of the class Betaproteobacteria and Gram-positive Peptococcaceae that had not before been linked to iron reduction (Kunapuli et al, 2007;Hori et al, 2010;Pilloni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Slobodkin et al [89] isolated thermophilic anaerobic archaea from petroleum reservoirs, which was capable of dissimilatory ferric iron reduction. Hori et al [92] demonstrated the involvement of archaea in ferric iron reduction in rice paddy soil by 13 C-acetate probing. Abundance of archaea with ferric iron reduction was low and ferric iron reduction by archaea would not be an important process.…”
Section: Interactions Of Microorganisms With Iron Oxidesmentioning
confidence: 99%